Illocutionary acts in Glimpse of Us by Joji - Zakariyya, Muhammad Zaki; Imperiani, Ernie D. A. (Passage: Journal of English Language and Literature, 2025)
This study analysed the types of illocutionary act and functions of the illocutionary act in the song lyrics of Glimpse of Us by Joji. The study used Creswell’s (2014) descriptive qualitative research design and Creswell’s (2014) documentation data collection method. After the data is collected, the data is analysed using the types of illocutionary acts by Searle and Bierwisch (2012) and the functions of illocutionary acts by Leech (2016). The study shows that there are three types of illocutionary acts found in the song lyrics – assertion, question, and request. Assertion type of illocutionary act was found as the most dominant type of illocutionary act with the frequency of 22 (70,52%), followed by question with 4 (14,81%), and request with 1 (3.71%). Additionally, there are four functions of illocutionary acts found in the song lyrics. Those are collaborative, convivial, conflictive, and competitive. Collaborative was the most dominant functions of illocutionary act with the frequency of 14 (51.85%) followed by convivial with 7 (25.93%), conflictive with 5 (18.51%) and competitive with 1 (3.71%). In the end, the study illuminates Joji's strategic use of illocutionary acts in Glimpse of Us, showcasing a delicate balance between conveying information and forging emotional connections, thereby contributing significantly to the song's overall richness and complexity of artistic expression within the realm of music.